The messianic reduction : Walter Benjamin and the shape of time - Fenves, Peter D. (Peter David), 1960- (Meridian (Stanford, Calif.), 2011)
The Messianic Reduction is a groundbreaking study of Walter Benjamin's thought. Fenves places Benjamin's early writings in the context of contemporaneous philosophy, with particular attention to the work of Bergson, Cohen, Husserl, Frege, and Heidegger. By concentrating on a neglected dimension of Benjamin's friendship with Gershom Scholem, who was a student of mathematics before he became a scholar of Jewish mysticism, Fenves shows how mathematical research informs Benjamin's reflections on the problem of historical time.